Mobile Instant Messaging as Collaborative Tool for Language Learning - Kasturi, Sivabalan; Zuraina, Ali (Universiti Malaysia Pahang, 2019)
In recent years, collaborative learning is commonly used in higher intuitions. One of the modes of collaborative learning is exploiting mobile phones specifically instant messaging to foster new possibilities for achieving more effective and attractive learning activities. Even though mobile phones have become valuable collaborative learning tools, but their substantial contributions to collaborative learning are still insufficient. The current study collated and correlated 40 journal articles published between 2015 and 2017 on mobile instant messaging as a collaborative tool in language learning at higher intuitions. A systematic review was conducted to investigate the effectiveness of mobile instant messaging as a collaborative tool for language learning. Numerous issues, such as exploration of the application, the research methods, participants, intervention duration, teaching method, collaborative learning strategies, impacts, and challenges were addressed. The outcomes revealed that mobile instant messaging improved student and lecturer collaboration, created effective distant learning opportunities, and increased students’ participation. Further, the results also provided insights on future research and practice such as recommendations on how to appropriately employ mobile phones specifically instant messaging in facilitating language learning. Additionally, some studies suggested the collaborative learning activities administered through mobile instant messaging should be planned carefully to guide students to experience more effective collaborative learning.